Distribution of High-Volume Shoulder Arthroplasty Surgeons in the United States: Data from the 2014 Medicare Provider Utilization and Payment Data Release. (21st September 2016) - Somerson, Jeremy S.; Stein, Brandon A.; Wirth, Michael A.
Abstract : Background: Access to total shoulder arthroplasty (TSA) may become a concern in the United States because of an aging and active population resulting in increased demand. As high-volume TSA surgeons have demonstrated superior outcomes, access to these surgeons is a matter of patient and public health policy interest. The release of the 2012 Medicare Provider Utilization and Payment Data Public Use File (MPUPD-PUF) in 2014 provided volume and reimbursement data for procedures performed by individual physicians participating in Medicare. This study analyzed surgeon prevalence, surgeon distribution, and factors associated with higher or lower surgeon prevalence in metropolitan areas. Methods: The MPUPD-PUF was reviewed for the 2012 calendar year, and data were extracted for all physicians who performed a minimum of 11 TSA procedures for Medicare beneficiaries. Physicians in each major metropolitan area (population of >1 million) were grouped together. Average reimbursement, number of high-volume TSA surgeons, and number of total procedures were calculated per major metropolitan area. The presence of an American Shoulder and Elbow Surgeons (ASES) fellowship program and mean geographic reimbursement were analyzed for association with the number of high-volume TSA surgeons. Results: The MPUPD-PUF included 774 surgeons across the United States who performed an annual minimum of 11 TSA procedures covered by Medicare, with a combined total of 19, 505 TSA procedures. Of these surgeons, 45% practiced within major metropolitan areas with a population of >1 million. Surgeons who had completed an ASES fellowship had a higher volume of procedural claims (median, 26; range, 11 to 120) compared with other surgeons (median, 17; range, 11 to 163; p < 0.001). The distribution among major metropolitan areas was highly unequal, and more surgeons were present in cities with an ASES fellowship program. Conclusions: Access to high-volume shoulder arthroplasty surgeons by the Medicare population is lacking in multiple major metropolitan areas in the United States because of the uneven distribution of these surgeons. The method of analysis in this study allows for opportunities to target training programs as well as placement of physicians to ensure access to high-volume shoulder arthroplasty surgeons.